ПРОЦЕС ЗАБЕЗПЕЧЕННЯ ЯКОСТІ ВИЩОЇ ОСВІТИ: ПІДГОТОВЧО-ЕКСПЕРИМЕНТАЛЬНИЙ ЕТАП СТАНОВЛЕННЯ - Білокопитов, Василь (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті висвітлено актуальність процесу забезпечення якості вищої освіти; показано початок зближення національних систем вищої освіти Європи щодо процесу забезпечення якості освіти; окреслено перші суттєві кроки щодо впровадження процесу забезпечення якості вищої освіти; проаналізовано фактори, що вплинули на швидкий темп розвитку процесу забезпечення якості; визначено основні вимоги щодо процесу забезпечення якості; наголошено на справжньому початку концентрації уваги європейської академічної спільноти на проблемах якості освіти. В статье высветлена актуальность процесса обеспечения качества высшего образования; показано начало сближения национальных систем высшего образования Европы в вопросе качества образования; отмечены первые существенные шаги относительно внедрения процесса обеспечения качества высшего образования; проанализированы факторы, которые повлияли на быстрый темп развития процесса обеспечения качества; определены основные требования к процессу обеспечения качества; акцентировано на действительном начале концентрации внимания европейского академического общества на проблемах качества образования. The problem of quality assurance of higher education was, is and alwayswill be relevant to the educational system of any country. A large amount of different information about quality has accumulated at the modern stage in the global community. Sometimes this information is diametrically different and it is difficult to comprehend and choose rational results for further effective use. Quality assurance as a separate sphere of activity, which was paid public attention at, appeared in the world at the end of the nineteenth century, when the first US organization for accreditation of higher education institutions appeared. Convergence of national systems of higher education in Europe took place in the mid 70’s. European countries borrowed the experience of the United States, and in 1984 the first quality assurance scheme started, because the size and number of higher education institutions began to demand more formal approach to quality management. France, the Netherlands and the United Kingdom were the first European countries where the mechanisms for quality assurance was introduced. The first important step to the implementation of quality assurance process was the creation of the international network of quality assurance agencies of higher education in 1991. The main purposes of the network are: The purposes of the Network are: to create, collect and disseminate information on current and developing theory and practice in the assessment, improvement and maintenance of quality in higher education; to undertake or commission research in areas relevant to quality in higher education; to express the collective views of its members on matters relevant to quality in higher education through contacts with international bodies and by other means; to promote the theory and practice of the improvement of quality in higher education; to provide advice and expertise to assist existing and emerging quality assurance agencies; to facilitate links between quality assurance agencies and support networks of quality assurance agencies; to assist members to determine the standards of institutions operating across national borders and facilitate better-informed international recognition of qualifications; to assist in the development and use of credit transfer and credit accumulation schemes to enhance the mobility of students between institutions (within and across national borders); to enable members to be alert to improper quality assurance practices and organisations; to organise, on request, reviews of the operation of members Internationally wellknown scholars of international trends in quality assurance C. Campbell and M. van der Wende have identified ten key factors that influenced the rapid development of quality assurance. The real beginning of European academic community concentration on issues of higher education quality was the creation of Council Recommendation on European Co-operation in Quality Assurance in Higher Education. European credit transfer system that ensured the validity of credits for those who want to continue their education in various higher educational institutions in Europe had a significant success.